VARIANTS OF DIALECTAL WORDS IN THE KARAKALPAK LANGUAGE - Kurbanbaeva, Bazargul Reimbaevna (SCIENCE and SOCIETY, 2026)
The article discusses dialectal words and the issue of variation. The use of phonetic and phonetic-lexical variants of dialectal words is analyzed based on the materials of the northern dialect.
Keywords: dialect; dialectal words; phonetic variants; phonetic-lexical variants